Update of the list of QPS‐recommended biological agents intentionally added to food or feed as notified to EFSA 15: suitability of taxonomic units notified to EFSA until September 2021 - EFSA Panel on Biological Hazards (BIOHAZ); Kostas Koutsoumanis; Ana Allende; Avelino Alvarez‐Ordóñez; Declan Bolton; Sara Bover‐Cid; Marianne Chemaly; Robert Davies; Alessandra De Cesare; Friederike Hilbert; Roland Lindqvist; Maarten Nauta; et al. (EFSA Journal, 2022)
Abstract The qualified presumption of safety (QPS) approach was developed to provide a generic pre‐evaluation of the safety of biological agents. The QPS approach is based on an assessment of published data for each agent, with respect to its taxonomic identity, the body of relevant knowledge and safety concerns. Safety concerns are, where possible, confirmed at the species/strain or product level and reflected by ‘qualifications’. The QPS list was updated in relation to the revised taxonomy of the genus Bacillus, to synonyms of yeast species and for the qualifications ‘absence of resistance to antimycotics’ and ‘only for production purposes’. Lactobacillus cellobiosus has been reclassified as Limosilactobacillus fermentum. In the period covered by this statement, no new information was found that would change the status of previously recommended QPS taxonomic units (TU)s. Of the 70 microorganisms notified to EFSA, 64 were not evaluated: 11 filamentous fungi, one oomycete, one Clostridium butyricum, one Enterococcus faecium, five Escherichia coli, one Streptomyces sp., one Bacillus nakamurai and 43 TUs that already had a QPS status. Six notifications, corresponding to six TUs were evaluated: Paenibacillus lentus was reassessed because an update was requested for the current mandate. Enterococcus lactis synonym Enterococcus xinjiangensis, Aurantiochytrium mangrovei synonym Schizochytrium mangrovei, Schizochytrium aggregatum, Chlamydomonas reinhardtii synonym Chlamydomonas smithii and Haematococcus lacustris synonym Haematococcus pluvialis were assessed for the first time. The following TUs were not recommended for QPS status: P. lentus due to a limited body of knowledge, E. lactis synonym E. xinjiangensis due to potential safety concerns, A. mangrovei synonym S. mangrovei, S. aggregatum and C. reinhardtii synonym C. smithii, due to lack of a body of knowledge on its occurrence in the food and feed chain. H. lacustris synonym H. pluvialis is recommended for QPS status with the qualification ‘for production purposes only’.